Assessing Genetic Diversity to Breed Competitive Biofortified Wheat With Enhanced Grain Zn and Fe Concentrations - Velu, Govindan; Crespo Herrera, Leonardo; Guzman, Carlos; Huerta, Julio; Payne, Thomas; Singh, Ravi P. (Frontiers in Plant Science, 2019)
Breeding wheat with enhanced levels of grain zinc (Zn) and iron (Fe) is a cost-effective, sustainable solution to malnutrition problems. Modern wheat varieties have limited variation in grain Zn and Fe, but large-scale screening has identified high levels of Zn and Fe in wild relatives and progenitors of cultivated wheat. The most promising sources of high Zn and Fe are einkorn (Triticum monococcum), wild emmer (T. dicoccoides), diploid progenitors of hexaploid wheat (such as Aegilops tauschii), T. spelta, T. polonicum and landraces of T. aestivum. This study evaluate the effects of translocations from rye and different Aegilops species in a ‘Pavon-76’ wheat genetic background and introduced into a wheat biofortification breeding program at CIMMYT that uses diverse genetic resources, including landraces, recreated synthetic hexaploids, T. spelta, and pre-breeding lines. Four translocations were identified that resulted significantly higher Zn content in ‘Pavon 76’ genetic background than the check varieties, and they had increased levels of grain Fe as well compared to ‘Pavon 76’. These lines were also included in the breeding program aimed to develop advanced high Zn breeding lines. Advanced lines derived from diverse crosses were screened under Zn-enriched soil conditions in Mexico during the 2017 and 2018 seasons. The Zn content of the grain was ranging from 35 to 69 mg/kg during 2017 and 38 -72 mg/kg during 2018. Meanwhile grain Fe ranged from 30 to 43 mg/kg during 2017 and 32 to 52 mg/kg during 2018. A highly significant positive correlation was found between Zn and Fe (r = 0.54; P <0.001) content of the breeding lines, therefore it was possible to breed for both properties in parallel. Yield testing of the advanced lines showed that 15% (2017) and 24% (2018) of the lines achieved 95-110% yield potential of the commercial checks and also had 12 mg/kg advantage in the Zn content suggesting that greater genetic gains and farmer-preferred wheat varieties were developed and deployed. A decade of research and breeding efforts led to the selection of ‘best-bet’ breeding lines and to the release of eight biofortified wheat varieties in target regions of South Asia and in Mexico.